Training physicians for the real world of medicine: administration-based learning. - Rosenstock, Jason; Sparks, Garrett M (Medical Education, 2016)
Tired of outdated teaching formats like case-based learning ( CBL), problem-based learning ( PBL) and team-based learning ( TBL)? We wanted something fresh for our medical school, something that would prepare our graduates for the modern practice of medicine, something that would satisfy regulatory agencies and our deans. After doing an extensive needs assessment, which we ignored, we decided to replace basic science in our curriculum with something more practical: administration-based learning ( ABL). We taught students how to fix fax machines, how to deal with angry team members, and how to maximise revenue in private practice - lessons that were well received and were more consistent with what physicians really need to learn to be effective practitioners. Educational outcomes have been positive, and although more research is needed, we call on other schools to add ABL tracks to their own curricula.